Health anxiety in Iranian university students: a scoping review - Mahsa Hosseini; Maedeh Moradi Farahani; Soheila Shamsikhani; Mahsa Rezaei (Babol University of Medical Sciences, 2023)
Background and Objective: Adolescent Anxiety disorder, as a form of mental disorder, results in the phenomenon of individuals developing a profound sense of fear towards illness. The development of research in the mental health of students and the impact of mental health on the performance and activities of students during and after their studies necessitate greater attention to this area. This study was conducted to review the studies conducted and identify research gaps. Methods: This scoping review was designed and implemented with the 5-step approach of Arksey & O'Malley. databases (Google Scholar ، SID، Magiran, PubMed, Web of Science) were searched to review articles in English and Persian according to the study inclusion criteria until October 2023. Findings: This study includes 28 related studies from 1384 to 1402. The largest number of studies are related to the years 1401 and 1400. The evaluated articles in the field of health anxiety were mainly descriptive and five different tools were used to evaluate health anxiety. This study shows that most of the studies were conducted in Tehran and most of the articles (57%) were published in domestic magazines in Persian. Conclusion: According to the results of the descriptive studies and the creation of a scientific foundation, it is recommended that standard and similar tools be used in future experimental studies to treat this attention-oriented disorder so that the results can be compared.